RECQ1 helicase is involved in replication stress survival and drug resistance in multiple myeloma - Viziteu, Elena; Seckinger, Anja; Goldschmidt, Hartmut; Hose, Dirk (Leukemia, 2017)
Multiple myeloma (MM) is a plasma cell cancer with poor survival, characterized by the expansion of multiple myeloma cells (MMCs) in the bone marrow. Using a microarray-based genome-wide screen for genes responding to DNA methyltransferases (DNMT) inhibition in MM cells, we identified RECQ1 among the most downregulated genes. RecQ helicases are DNA unwinding enzymes involved in the maintenance of chromosome stability. Here we show that RECQ1 is significantly overexpressed in MMCs compared to normal plasma cells and that increased RECQ1 expression is associated with poor prognosis in three independent cohorts of patients. Interestingly, RECQ1 knockdown inhibits cells growth and induces apoptosis in MMCs. Moreover, RECQ1 depletion promotes the development of DNA double-strand breaks, as evidenced by the formation of 53BP1 foci and the phosphorylation of ataxia-telangiectasia mutated (ATM) and histone variant H2A.X (H2AX). In contrast, RECQ1 overexpression protects MMCs from melphalan and bortezomib cytotoxicity. RECQ1 interacts with PARP1 in MMCs exposed to treatment and RECQ1 depletion sensitizes MMCs to poly(ADP-ribose) polymerase (PARP) inhibitor. DNMT inhibitor treatment results in RECQ1 downregulation through miR-203 deregulation in MMC. Altogether, these data suggest that association of DNA damaging agents and/or PARP inhibitors with DNMT inhibitors may represent a therapeutic approach in patients with high RECQ1 expression associated with a poor prognosis.